Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.iecr.8b00125
|View full text |Cite
|
Sign up to set email alerts
|

Colored Poly(vinyl chloride) by Femtosecond Laser Machining

Abstract: Colored poly­(vinyl chloride) (PVC) was fabricated by femtosecond laser micromachining without the addition of chemical colorants, eliminating the concern of leaching dyes and pigments. We determined that the changes in surface chemistry and surface topography both contribute to the observed yellow, brown, and black color formation. X-ray photoelectron spectroscopy (XPS) on the machined samples showed that conjugated double bonds are liable for the yellow and brown colors, whereas the presence of oxidized carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Due to excellent heat resistance, high chemical stability, resistant ability to most acid and alkali corrosions, and good processability, PP and its composite materials have been widely used in automobiles, packaging, membrane separation and pipelines, and other fields. Generally, the surface of PP products needs to be marked with patterns and texts such as two-dimensional (2D) codes and serial numbers to indicate the production date, company logo, the product expiration date, and anticounterfeiting functions. Usually, ink printing is used to produce these marks on the surface of the material, but there is the use of toxic and harmful reagents, the process flow is complicated, and there are serious environmental pollution problems. , In recent years, laser marking technology has emerged as a new type of printing technology that uses high-energy lasers to mark the surface of materials to form patterns, text, crystalline and self-assembly structures, and morphology. For example, Park et al reported the laser-directed supramolecular assembly of sub-5 nm columnar structures with adjustable orientation control. The high energy of the laser causes the matrix resin to be heated and carbonized, forming a clear pattern , of carbonization and blackening on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Due to excellent heat resistance, high chemical stability, resistant ability to most acid and alkali corrosions, and good processability, PP and its composite materials have been widely used in automobiles, packaging, membrane separation and pipelines, and other fields. Generally, the surface of PP products needs to be marked with patterns and texts such as two-dimensional (2D) codes and serial numbers to indicate the production date, company logo, the product expiration date, and anticounterfeiting functions. Usually, ink printing is used to produce these marks on the surface of the material, but there is the use of toxic and harmful reagents, the process flow is complicated, and there are serious environmental pollution problems. , In recent years, laser marking technology has emerged as a new type of printing technology that uses high-energy lasers to mark the surface of materials to form patterns, text, crystalline and self-assembly structures, and morphology. For example, Park et al reported the laser-directed supramolecular assembly of sub-5 nm columnar structures with adjustable orientation control. The high energy of the laser causes the matrix resin to be heated and carbonized, forming a clear pattern , of carbonization and blackening on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Laser marking technology has been widely used in the marking and patterning of material surfaces due to its rapid, efficient, and environmentally friendly advantages. Due to the wide variety of polymer materials having different structures and compositions, their laser response performance and the clarity and contrast of laser marking also show differences. ABS has excellent chemical stability and mechanical properties, but ABS is not a very good absorber of the near-infrared laser, leading to the blurred laser marking .…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchically structured surfaces with well-defined textures play very significant roles in sophisticated applications in sensors [1], photonics [2], tissue engineering [3], and superhydrophobic materials [4][5][6][7][8][9][10][11][12]. Generally, these surfaces are prepared in several steps combining mechanical, laser machining, physicochemical, and plasma technologies [13][14][15][16]. The so-called "breath figures" is one of the very popular and promising approaches [17][18][19].…”
Section: Introductionmentioning
confidence: 99%